2004
DOI: 10.1002/marc.200400230
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Facile Method for the Preparation of Uniform, Reactive Maleic Anhydride/Vinyl Acetate Copolymer Micro‐ and Nanospheres

Abstract: Summary: A novel, stabilizer‐free dispersion polymerization with alkyl esters as reaction media gives uniform alternating microspheres of maleic anhydride (MAn)/vinyl acetate (VAc) copolymer. The diameter of the copolymer microspheres could be precisely controlled from 80 to 750 nm by changing the monomer concentration or feed ratio. Moreover, this new type of copolymer microspheres with reactive anhydride groups on the surface has good solubility in common nontoxic solvents such as water and ethanol.SEM image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 31 publications
3
85
0
Order By: Relevance
“…39,40 In a typical experiment, the monomers MAH (2.45 g, 25 mmol) and St (1.3 g, 12.5 mmol), the initiator azobisisobutyronitrile (AIBN; 37.5 mg, 1 wt % relative to the monomers) and the solvent isopentyl acetate (25 ml) were added to a 100 ml three-necked flask.…”
Section: Experimental Procedures Preparation Of the Pms Templatementioning
confidence: 99%
See 1 more Smart Citation
“…39,40 In a typical experiment, the monomers MAH (2.45 g, 25 mmol) and St (1.3 g, 12.5 mmol), the initiator azobisisobutyronitrile (AIBN; 37.5 mg, 1 wt % relative to the monomers) and the solvent isopentyl acetate (25 ml) were added to a 100 ml three-necked flask.…”
Section: Experimental Procedures Preparation Of the Pms Templatementioning
confidence: 99%
“…This process is an improvement over our previously developed 'stabilizer-free precipitation polymerization' for core-shell polymer particles and consequent removal of the template core by solvent etching. 39,40 Excess MAH was added into the reaction system at the very beginning of the reaction. After the alternating copolymerization of MAH and styrene (St), residual MAH monomer is present along with the monodisperse poly(MAH-alt-St) (PMS) nanoparticles formed in the reaction system.…”
Section: Introductionmentioning
confidence: 99%
“…[9,12,15] This may be attributed to the facile alternating copolymerization of MAn and VAc by a charge transfer complex (CTC) mechanism, as has been discussed in detail in our previous articles. [19,20] However, we found that the ultimate conversion of monomer was hard to be completed (around 80-90%). This can be interpreted from the phenomenon of phase separation in the dispersion polymerization process, which may lead to the ratio imbalance of MAn and VAc (i.e., beyond 1:1).…”
Section: Typical Kinetic Charactermentioning
confidence: 92%
“…[19,20] In comparison, the solution copolymerization of MAn and VAc in methyl propyl ketone was also conducted (with the standard recipe in Table 1, except that the solvent was replaced).…”
Section: Polymerization Proceduresmentioning
confidence: 99%
See 1 more Smart Citation